A comparative synthesis of ZSM-5 with ethanol or TPABr template: distinction of Brønsted/Lewis acidity ratio and its impact on n-hexane cracking. Issue 7 (19th March 2018) - Ma, Tong; Zhang, Luoming; Song, Yu; Shang, Yunshan; Zhai, Yanliang; Gong, Yanjun
Abstract : ZSM-5 by EtOH, possessing an ultra-high Brønsted/Lewis acidity ratio, has a long lifetime and suppresses coke deposit during n -hexane cracking. Abstract : Two kinds of ZSM-5 zeolites with various SiO2 /Al2 O3 ratios were synthesized using ethanol (EtOH) or tetrapropylammonium bromide (TPABr) as the template respectively and their physicochemical properties were investigated extensively. Different ZSM-5 morphologies were observed for each kind of sample, the former with coffin-shaped single crystals and the latter with aggregates assembled from nanocrystals. The desilication process occurred and intensified at a later period of crystallization for ZSM-5 by EtOH with increasing SiO2 /Al2 O3 ratio and/or increasing alkalinity, due to its weaker pore-filling effect. Specifically, ZSM-5 zeolites by EtOH had a large amount of Brønsted acid sites (BAS) and a much less amount of Lewis acid sites (LAS), leading to an ultra-high B/L ratio (45–66); while those by TPA + with comparable acidity possessed a usual B/L ratio (6–8). Owing to no octahedrally coordinated Al in both kinds of ZSM-5, the amount of LAS should be attributed to the tri-coordinated Al "defect" sites, in accordance with the extra silanols determined by OH-IR. Further, ZSM-5 by EtOH exhibited fewer internal defective Al sites, which was responsible for its small number of LAS. Applied to n -hexane cracking, the ZSM-5 zeolite by EtOH had high activity with twice the lifetime (60 vs. 35 h) compared to that by TPA + with a similar SiO2 /Al2 O3 ratio. The ratio of accumulated amount of coke to converted n -hexane was obtained as a measure of average coke selectivity ( S c ). The ZSM-5 zeolites by EtOH displayed less than half the S c value (0.45) in comparison with those by TPA + (1.08), due to the big difference in LAS, regardless of their SiO2 /Al2 O3 ratio, morphological structure and reaction conditions. Thus, for ZSM-5 possessing a high B/L ratio improves the catalytic activity and decreases coke deposit through suppressing the dehydrogenation process of the reaction intermediate to form coke precursor.